Decoding the historical tale: COVID-19 impact on haematological malignancy patients-EPICOVIDEHA insights from 2020 to 2022 - Salmanton-García, Jon; Marchesi, Francesco; Farina, Francesca; Weinbergerová, Barbora; Itri, Federico; Dávila-Valls, Julio; Martín-Pérez, Sonia; Glenthøj, Andreas; Hersby, Ditte Stampe; Gomes da Silva, Maria; Nunes Rodrigues, Raquel; López-García, Alberto; et al. (EClinicalMedicine, 2024)
BACKGROUND: The COVID-19 pandemic heightened risks for individuals with hematological malignancies due to compromised immune systems, leading to more severe outcomes and increased mortality. While interventions like vaccines, targeted antivirals, and monoclonal antibodies have been effective for the general population, their benefits for these patients may not be as pronounced. METHODS: The EPICOVIDEHA registry (National Clinical Trials Identifier, NCT04733729) gathers COVID-19 data from hematological malignancy patients since the pandemic's start worldwide. It spans various global locations, allowing comprehensive analysis over the first three years (2020-2022). FINDINGS: The EPICOVIDEHA registry collected data from January 2020 to December 2022, involving 8767 COVID-19 cases in hematological malignancy patients from 152 centers across 41 countries, with 42% being female. Over this period, there was a significant reduction in critical infections and an overall decrease in mortality from 29% to 4%. However, hospitalization, particularly in the ICU, remained associated with higher mortality rates. Factors contributing to increased mortality included age, multiple comorbidities, active malignancy at COVID-19 onset, pulmonary symptoms, and hospitalization. On the positive side, vaccination with one to two doses or three or more doses, as well as encountering COVID-19 in 2022, were associated with improved survival. INTERPRETATION: Patients with hematological malignancies still face elevated risks, despite reductions in critical infections and overall mortality rates over time. Hospitalization, especially in ICUs, remains a significant concern. The study underscores the importance of vaccination and the timing of COVID-19 exposure in 2022 for enhanced survival in this patient group. Ongoing monitoring and targeted interventions are essential to support this vulnerable population, emphasizing the critical role of timely diagnosis and prompt treatment in preventing severe COVID-19 cases. FUNDING: Not applicable.